EFEKTIVITAS PENATAAN ORGANISASI SEKRETARIAT DAERAH KOTA TOMOHON - ROMPIS, FRANDO; Laloma, Alden; Plangiten, Novva (Sam Ratulangi University, 2015)
ABSTRACT : Since the enactment of PP. 41 Year 2007 on Regional Perengkat organizations, localgovernments Tomohon has conducted reorganization regional secretariat. Accordingly, this research toknow